2020
DOI: 10.1680/jmacr.18.00116
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature mechanical properties of calcium sulfate whisker-reinforced high-alumina cement

Abstract: Brittleness and low flexural or tensile strength limit the applications of calcium aluminate cement (CAC)-based composites in high-temperature oil or gas well cementing. The reinforcement of the CAC with whiskers substantially enhances its strength and toughness and is a sophisticated approach to overcome the mechanical limitations of the CAC. In this study, the effect of calcium sulfate whiskers (CSWs) on the mechanical properties of the CAC-based composites was investigated; six cement specimens, with whiske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Before exposure to high temperatures, both the compressive strength and exural strength of CaCO 3 whiskerbased specimen were improved rapidly with the increase in CaCO 3 whisker content until this content was up to 10 wt.%; thereafter, the strength enhancement was negatively correlated with the increase in CaCO 3 whisker content, as shown in Figures 3(a) and 4(a). e reason why the strength decreased when the CaCO 3 whisker content was over 10 wt.% may be related to the aggregation of CaCO 3 whisker, which leads to the generation of a heterogeneous microstructure, thereby lowering the overall strength of CaCO 3 whisker-based specimen [13]. In addition, the increase in CaCO 3 whisker content may result in a relatively weak bond between cement paste and CaCO 3 whisker, and thus reducing the strength of CaCO 3 whisker-based specimen.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Before exposure to high temperatures, both the compressive strength and exural strength of CaCO 3 whiskerbased specimen were improved rapidly with the increase in CaCO 3 whisker content until this content was up to 10 wt.%; thereafter, the strength enhancement was negatively correlated with the increase in CaCO 3 whisker content, as shown in Figures 3(a) and 4(a). e reason why the strength decreased when the CaCO 3 whisker content was over 10 wt.% may be related to the aggregation of CaCO 3 whisker, which leads to the generation of a heterogeneous microstructure, thereby lowering the overall strength of CaCO 3 whisker-based specimen [13]. In addition, the increase in CaCO 3 whisker content may result in a relatively weak bond between cement paste and CaCO 3 whisker, and thus reducing the strength of CaCO 3 whisker-based specimen.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Whiskers can be categorized as organic and inorganic whiskers, and organic whisker such as cellulosic whisker is frequently used for reinforcing the polymer materials [6,7]. With respect to inorganic whisker, calcium carbonate whisker [8][9][10][11][12], calcium sulphate whisker [13], zinc oxide whisker [14], silicon carbide whisker [15], and potassium titanate whisker [16] are commonly used, and among which, CaCO 3 whisker has the most extensive application in the reinforcement of cementitious materials. Previous studies have shown that CaCO 3 whisker has the capacity to improve the mechanical strength and enhance the flexural toughness of cementitious materials.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is necessary to find out if there is a chemical interaction between the whisker and cement paste. Third, Cheng et al [ 25 ] investigated the effect of CSW on the high-temperature mechanical properties of calcium aluminate cement-based composites. They found that CSW formed a stable phase and deflected cracks to improve the toughness of the cement binders.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, CSHW has a strong market competitiveness as its price is only 1/200–1/300 of SiC, and it is easy for surface treatment. Therefore, CSHW have been widely used in papermaking, plastic, resin, rubber, friction materials, lightweight building materials and other fields [ 5 , 6 ]. The most important parameters of CSHW are the diameter and the aspect ratio, which have significant influence on the comprehensive performance of CSHW.…”
Section: Introductionmentioning
confidence: 99%